7-OH quinoline Schiff bases: are they the long awaited tautomeric bistable switches?. (November 2021) - Georgiev, Anton; Yordanov, Dancho; Ivanova, Nikoleta; Deneva, Vera; Vassilev, Nikolay; Kamounah, Fadhil S.; Pittelkow, Michael; Crochet, Aurelien; Fromm, Katharina M.; Antonov, Liudmil
Abstract: Two novel, 7-hydroxyquinoline based, Schiff bases have been synthesized and their spectral properties have been investigated by combined use of optical and NMR spectroscopy and theoretical DFT calculations. The results indicate that 8-((phenylimino)methyl)quinolin-7-ol exists as a mixture of enol and two keto tautomers in solution, while 8-(((pentarfluorophenyl)imino)methyl)quinolin-7-ol is presented as a single enol form. Upon irradiation, in both compounds, through excited state intramolecular proton transfer mechanism, a rotation around the Cquin -CH bond occurs, indicating that they are suitable to be used as bistable switches. The back relaxation is faster comparing to the theoretical expectations, due to the additional flexibility around the azomethine bond. As a result of forming complexes with the acidic counter ion, no intramolecular rotation happens upon protonation with trifluoroacetic acid. Graphical abstract: Image 1 Highlights: Two new 7-OH quinoline Schiff bases, containing C6 H5 and C6 F5 groups, are designed. The first one exists as a mixture of enol and two keto forms in solution. The second one is presented solely as an enol tautomer. Z/E switching, assisted by ESIPT, is observed upon irradiation. The relaxation back is faster due to flexibility of the azomethyne part.